Keberadaan Kelompok Minoritas: Mitos Homogenitas Bangsa Jepang - Widiandari, Arsi (Vocational College of Diponegoro University, 2021)
The focus of this research is to discus the existence of minority groups in Japan. The existence of this minority community breaks the understanding of the Japanese nation which consists of a homogeneous society. This study uses the library method, by taking data from various literatures such as scientific articles, reference books and official reports issued by the Japanese Government through official website. This study found that existence of minority community in Japan for example Zainichi Korea, Burakumin groups, Ainu and a number of migrant worker is proof that Japan is not a homogeneous society but is a multicultural society. This paper is expected to complement the research that has been done previously related to the identity of the Japanese nation.